A new alkaloid from Portulaca oleracea L. and its anti-inflammatory activity. Issue 18 (8th September 2022) - Liu, Fangxuan; Cui, Xinyu; Duan, Yang; Guo, Shengnan; Liu, Jinpeng; Ying, Xixiang
Abstract: A new alkaloid, identified as ( E )-2-(4-hydroxyphenyl)-3-(pyridazin-3-yl)-acrylaldehyde, named oleradazine, was isolated from Portulaca oleracea L., and the structure was elucidated using spectroscopic methods, including 1D and 2D NMR spectroscopic and UHPLC-ESI-QTOF/MS methods. In addition, the compound was used to investigate its anti-inflammatory activity in lipopolysaccharide-stimulated macrophages. It was suggested that the oleradazine can significantly inhibit the inflammatory factors, interleukin 1 β and nitric oxide in lipopolysaccharide-stimulated RAW 264.7 cells by enzyme-linked immunosorbent assays. Graphical Abstract: UF0001